Effect of dentin laser irradiation at different pulse settings on microtensile bond strength of flowable resin - Buyukhatipoglu, Isil; ÖZSEVİK, ABDÜL SEMİH; SEÇİLMİŞ, ASLI; Usumez, Aslihan (My University, 2016)
The aim of this study was to compare the effect of Er:YAG laser irradiation and adhesive systems on the microtensile bond strength (mu TBS) of flowable resin to dentin. The flat dentin surfaces of 30 wisdom molar teeth were randomly divided into 3 groups (n=10): no laser etching (control), laser etching using QSP and MSP modes. After the application of the flowable and the composite resin, and 5,000 thermal aging, the mu TBS results were analyzed with two-way analysis of variance and Tukey-s honest standard of difference (HSD) tests. There Were no significant differences between the mu TBS of the self-etch group and the total-etch groups for MSP (p>0.05). MSP mode is a useful pulse mode for dentin surface treatment due to elimination of the acid-etching step.